Pengaruh Penghargaan Finansial, Pelatihan Profesional, dan Pengakuan Profesional Terhadap Pemilihan Karir Sebagai Akuntan Publik Bagi Mahasiswa Akuntansi - Alfian Fatkhur Hidayat; Wahyono Wahyono (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The career choice of accounting students as public accountants can beinfluenced by several factors, including financial rewards,professional training, and professional recognition. The purpose ofthis research is to analyze and obtain empirical evidence about theeffect of financial rewards, professional training, and professionalrecognition on career choices as public accountants. This research isa quantitative descriptive study using primary data in the form of aquestionnaire distributed to students majoring in Accounting at theMuhammadiyah University of Surakarta. The results showed thatfinancial rewards and professional training had no effect (statisticallyinsignificant) on career choices as public accountants, whileprofessional recognition had a significant effect (statisticallysignificant) on career choices as public accountants for UMSaccounting students.